Method Textbooks for Primary School Education in Schools (Journal of Pedagogical Inventions and Practices, 2022)
In this article, the methods of the pilgrims during the colonial era were the textbooks, its content, and the textbooks it created for elementary school students to learn in schools about the importance of books devoted to the intended education.